Pancreas: Do All Roads Lead to Mitochondria? - Amit Mukherji; Omobola Onikoy; Vasudeva G. Kamath (Pancreas, 2025)
Over several millions of years of evolution, mitochondria have transformed into spe-cialized organelles. Today, they cannot live outside the cell nor can the host cell live without them, resulting in a symbiotic relationship. Richard Altmann, in 1894, documented them as cell organelles and called them “bioblasts”. Later, the term “mitochondria” itself was coined by Carl Benda in 1898. Ever since these findings, we in the field of medicine have learned a lot about this tiny organelle, but numerous aspects continue to be discovered. In this article, we will review the significance of this organelle in terms of pancreatic dysfunctions.